Rekonstruksi Subjektivitas Perempuan - Auliya Habibah (Jurnal ICMES, 2026)
Saudi Vision 2030 integrates women into the post-oil development agenda as an effort to address the crisis of the rentier economic structure. This study aims to analyze the reconstruction of women’s subjectivity in Saudi Vision 2030 amid the tension between Wahhabi orthodoxy and the post-oil development transformation agenda. Using Spivak’s postcolonial feminist perspective, this study argues that the integration of women into the economic participation under Saudi Vision 2030 does not merely reflect an emancipation project, but is part of the state’s strategy in responding to the rentier economic crisis. The representation of women as subjects of development tends to be instrumental and has the potential to distort women’s agency itself. This study employs a qualitative approach using a single-case study method and a literature review. The findings reveal that the state reconstructs women’s subjectivity through the production of development discourses, the top-down institutionalization of policies, and the restriction of women’s political spaces. This process involves the co-optation of Wahhabi religious authorities to maintain social legitimacy. This study is significant because it critiques the narrative of gender reform, which is often viewed as a form of “progressivism.” Gender transformation within Saudi Vision 2030 must be understood as an adaptation of social structures to post-oil economic demands, as well as a political instrument to strengthen state control over societal and political dynamics. Thus, this study emphasizes the importance of positioning women as autonomous political subjects to achieve holistic gender equality.